The Effect of Giving Lemon Aromatherapy to Reduce Nausea and Vomiting in Pregnant Women in the 1st Trimester in the Working Area of Sukaraja Tiga Health Center, East Lampung - Rosalia Pertiwi; Richta Puspita Haryanti; Amalia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Symptoms of nausea and vomiting during pregnancy, often referred to as